Efficacy of Spinal Cord Stimulation for Failed Back Surgery Syndrome in Elderly Patients: A Retrospective Study - Naoki Higashiyama; Shinya Tamura; Taku Sugawara (Pain Research and Management)
Objectives. Failed back surgery syndrome (FBSS) refers to a condition where symptoms such as low back pain, leg pain, and numbness persist or recur after lumbar surgery; it has been reported to occur in 10%–40% of patients who have undergone lumbar surgery. Spinal cord stimulation (SCS) has been reported useful for low back and leg pain due to FBSS. In this study, we studied the efficacy and safety of SCS for FBSS in older adults. Methods. Among FBSS patients who underwent an SCS trial between November 2017 and December 2020, those with at least 50% pain reduction during the trial phase who requested spinal cord stimulator implantation underwent implantation of a stimulator under local anesthesia. The patients were divided into two groups: patients aged <75 years (<75-year-old group) and patients aged ≥75 years (≥75-year-old group). The male/female ratio, symptom duration, operative duration, visual analog scale (VAS) scores before and after one year of surgery, responder rate (RR), complications one year after surgery, and stimulator removal rate were analyzed. Results. There were 27 cases in the <75-year-old group and 46 in the ≥75-year-old group, with no significant differences in male/female ratio, duration of pain, or operative time between the two groups. VAS scores for low back pain, leg pain, and overall pain one year after surgery were improved significantly from respective preoperative scores in both groups P<0.001. There were no significant differences in low back pain VAS, leg pain VAS, overall pain VAS, RR, complications one year after surgery, or stimulator removal rate between the two groups. Conclusion. SCS reduced pain effectively in both <75-year-old and ≥75-year-old groups with no differences in complications. Therefore, spinal cord stimulator implantation was considered a viable option for FBSS treatment in older adults because it can be performed under local anesthesia and is associated with a low incidence of complications.